INJURY PATTERNS IN FATAL ROAD TRAFFIC ACCIDENTS AT IMPHAL, MANIPUR- A RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2025)
Road traffic accidents (RTAs) are a global issue, and the specific statistics, regulations, and preventive measures may vary with country or region. RTAs are often caused by factors such as human error, poor road conditions, mechanical failures, environmental factors, or infrastructure issues. The present retrospective study was conducted in Jawaharlal Nehru Institute of Medical Sciences (JNIMS) Imphal mortuary between January 2019 and April 2022. A total of 172 fatal road traffic accident incidences had been reported in JNIMS Imphal mortuary during this period. The study focused on the pattern of injuries sustained by the victims, with a particular emphasis on gender distribution and age groups. Various types of mechanical injuries were examined, including fractures and their impact on vital organs. The study also investigated the major causes of death among road traffic accident victims.
Keywords: Road traffic accidents; Mechanical injuries; Cause of death